Increased anatomic severity in appendicitis is associated with outcomes in a South African population. Issue 1 (July 2017) - Hernandez, Matthew C.; Kong, Victor Y.; Aho, Johnathon M.; Bruce, John L.; Polites, Stephanie F.; Laing, Grant L.; Zielinski, Martin D.; Clarke, Damian L.
Abstract : BACKGROUND: Severity of emergency general surgery (EGS) diseases has not been standardized until recently. The American Association for the Surgery of Trauma (AAST) proposed an anatomic severity grading system for EGS diseases to facilitate communication and quality comparisons between providers and hospitals. Previous work has demonstrated validity of the system for appendicitis in the United States. To demonstrate generalizability, we aim to externally validate this grading system in South African patients with appendicitis. METHODS: Patients with acute appendicitis during 2010 to 2016 were identified at multi-institutional sites within South Africa. Baseline demographics and procedure types were recorded, and AAST grades were assigned based on intraoperative findings. Outcomes included duration of stay, mortality, and Clavien-Dindo complications. Summary statistical univariate and nominal logistic regression analyses were performed to compare AAST grade and outcomes. RESULTS: A total of 1, 415 patients with a median (interquartile range) age of 19 years (14–28 years) were included (55% men). One hundred percent underwent appendectomy: 63.5% completed via midline laparotomy, 36.5% via limited incision (31.8% via McBurney incision and 4.7% via laparoscopy). Overall, 30-day mortality rate was 1.4% with an overall complication rate of 44%. Most common complications included surgical site infection (n = 147, 10.4%), pneumonia (n = 105, 7.4%), and renal failure (n = 64, 4.5%). Distribution of AAST grade is as follows: Grade 0 (10, 0.7%), Grade 1 (247, 17.4%), Grade 2 (280, 19.8%), Grade 3 (158, 11.3%), Grade 4 (179, 12.6%), and Grade 5 (541, 38.2%). Increased median (interquartile range) AAST grades were recorded in patients with complications, 5 (3–5) compared with those without (2 [1–3], p = 0.001). Duration of stay was increased for patients with higher AAST grades: 4 and 5 (10.6 ± 5.9 days) versus I and II (3.6 ± 4.3 days; p = 0.001). Area under the receiver operating characteristic analysis to predict presence of any complication based on AAST grade was 0.90. CONCLUSION: The AAST EGS grading system is valid to predict important clinical outcomes in a South African population with an increased degree of severity on presentation. These results support generalizability of the AAST EGS grading system for appendicitis in a developing nation. LEVEL OF EVIDENCE: Prognostic, level II.